Manajemen Botol Susu Dipengaruhi Oleh Tingkat Pendidikan, Pengetahuan Dan Sikap Ibu Bayi/Balita - Ana Silvia; Rahmawati Rahmawati; Erminawati Erminawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstract Milk Bottle Management Affected By Level Of Education, Knowledge And Attitude Of Baby/Baby Mother. Management of milk bottles is a maintenance measure for milk bottles. Milk bottle management is a personal management that is carried out individually by mothers. Deficiencies in milk bottle management can be influenced by the level of education, knowledge, and attitude of a person. The purpose of this study was to determine the relationship of education, knowledge, and attitude with the management of milk bottles by mothers in Kelurahan Cempaka. The type of this research was analytic survey with cross sectional design. The sample in this study were mothers who had babies or toddlers using milk bottles in the provision of drinks totaling 96 mothers. The sampling technique used Purposive sampling. Data analyzed using the Spearman test. The results showed that there was a relationship between education and milk bottle mangement (p 0.007